HOMICIDAL DEATHS IN VARANASI REGION (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
The present study was undertaken in the Department of Forensic Medicine, Banaras Hindu University, Varanasi to find out the incidence of homicide and aftermaths of incidence with reference to crime investigation in terms of time and place of incidence, information to police and their arrival, medical aid, dying declaration and other criminological aspects.
Keywords: Durkheim's; solidarity